Prinsip Sopan Santun dalam Wacana Iklan Pilkada pada Surat Kabar Harian Solopos, Jateng Pos, dan Wawasan Edisi November-Desember 2015 untuk Media Pembelajaran Menulis Teks Persuasi Kelas X SMK - Nafisah, Nidiatika Raidah Fati (2016)
This research has three aims. (1) describe the application of maxims on the principle of courtesy (2) to explain the forms of speech (3) to find out the implementation of advertisement about local election on daily newspaper "Solopos, Jateng, and Wawasan post for edition of November -December 2015 as a learning media to write persuasion text for Vocational Students grade X. The type of this research is a qualitative descriptive. The source of data used for this study is advertisement about local election on daily newspaper . Data obtained from the writings on the ads about the elections in which there is principle of politeness and a form of speech in advertisement on the daily newspaper Solopos, Jateng Post, and Wawasan post for edition of November -December 2015. The techniques of Data collection used in this research is the checking out and making a note. The technique of data analysis used in this study using the method of indeterminate extra lingual. The results of this study demonstrate the principles of courtesy, forms of speech and implementation for learning media on the advertisement texts about local election on daily newspaper "Solopos, Jateng Post, and Wawasan post for edition of November -December 2015. The principle of courtesy found in the research include : (1) maxim of wisdom; (2) maxim of generosity; (3) maxim Award; (4) the maxim of simplicity; (5) maxim of conspiracy; (6) maxim of sympathy. While the form of utterance found in this research include (1) commisive form of speech; (2) imposive form of speech; (3) expressive form of speech; and (4) assesive form of utterance. The implementation for learning media on the advertisement texts about local election on daily newspaper "Solopos, Jateng post, and Wawasan for edition of November -December 2015 which are in the form of speech and politeness principle as a learning media for persuasion text for Vocational Students grade X. Keywords: maxim, speech, and newspaper